Prevalence, Trends and Associated Socio-Economic Factors of Obesity in South Asia - Jayawardena, R.; Byrne, N.; Soares, Mario; Katulanda, P.; Hills, A. (S. Karger AG, 2013)
Aim: Worldwide obesity levels have increased unprecedentedly over the past couple of decades. Although the prevalence, trends and associated socio-economic factors of the condition have been extensively reported in Western populations, less is known regarding South Asian populations. Methods: A review of articles using Medline with combinations of the MeSH terms: 'Obesity', ‘Overweight’ and ‘Abdominal Obesity’ limiting to epidemiology and South Asian countries. Results: Despite methodological heterogeneity and variation according to country, area of residence and gender, the most recent nationally representative and large regional data demonstrates that without any doubt there is an epidemic of obesity, overweight and abdominal obesity in South Asian countries. Prevalence estimates of overweight and obesity (based on Asian cut-offs: overweight ≥ 23 kg/m[superscript]2, obesity ≥ 25 kg/m[superscript]2) ranged from 3.5% in rural Bangladesh to over 65% in the Maldives. Abdominal obesity was more prevalent than general obesity in both sexes in this ethnic group. Countries with the lowest prevalence had the highest upward trend of obesity. Socio-economic factors associated with greater obesity in the region included female gender, middle age, urban residence, higher educational and economic status. Conclusion: South Asia is significantly affected by the obesity epidemic. Collaborative public health interventions to reverse these trends need to be mindful of many socio-economic constraints in order to provide long-term solutions.